An Analytical Study of Pre-Trial Processes in Speedy Disposal of Cases in the Criminal Justice System of Malaysia - Ali, Sadaqut; Razi, Muhammad (International Journal of Criminology and Sociology, 2022)
This paper is an attempt to analyse the role of pre-trial processes in the criminal justice system in Malaysia as far as the speedy justice is concerned. Before 2010, Malaysia faced a huge backlog of criminal cases in the court; however, it made amendments in the code of criminal procedure and introduced the pre-trial processes in the criminal justice system of Malaysia to resolve the huge backlog and to promote the speedy trial. The researcher in this research has determined and explored that how pre-trial processes work in the way of disposal of criminal justice, and how it has reduced the huge backlog of criminal cases from the courts. The researcher has explained many case laws, provisions of criminal procedure code and described the opinions of judges and legal entities in Malaysia.